Cardio- and neuroprotective effects by pretreatment of dietary moringin from Moringa oleifera seeds and α-CD/moringin formulation in a rat model of isoproterenol-induced myocardial infarction - Razis, Ahmad Faizal Abdull; Kamal, Ramla Muhammad; De Nicola, Gina Rosalinda; Montaut, Sabine; Perimal, Enoch Kumar; Ahmad, Hafandi; Rollin, Patrick; Rigaud, Sébastien; Mazzon, Emanuela; Djedaini-Pilard, Florence (Cambridge University Press, 2025)
The aim of this study was to investigated the cardio- and neuroprotective effects of moringin (MG), a dietary isothiocyanate derived from Moringa oleifera seeds, in a rat model of isoproterenol (ISP)-induced myocardial infarction (MI). Thirty-two adult male Sprague Dawley rats were divided into four groups: a control group, an MI group, a group pretreated with freshly prepared MG solution (MG + MI; glucomoringin 20 mg/kg + 30 µl myrosinase/rat), and a group pretreated with a stable α-cyclodextrin-based formulation of MG (α-CD/MG + MI, 42 mg/kg). Pretreatments were administered daily for seven days, followed by ISP injections (85 mg/kg, subcutaneously) on days six and seven at 24-hour intervals to induce MI. The MI group showed impaired hemodynamic and behavioral responses, elevated malondialdehyde (MDA) levels, and decreased activity of antioxidant enzymes—superoxide dismutase (SOD) and catalase (CAT)—in both myocardial and hippocampal tissues. In addition, serum levels of cardiac biomarkers, including cardiac troponin I (cTnI) and creatine kinase myocardial band (CK-MB), were significantly increased. Pretreatment with MG and α-CD/MG markedly improved locomotor and exploratory behavior, reduced heart rate (HR), and enhanced mean arterial pressure (MAP). Both treatments also decreased serum cardiac marker levels, restored antioxidant enzyme activity, normalized brain monoamine concentrations, and improved the structural integrity of myocardial and hippocampal tissues. These findings indicate that MG and α-CD/MG confer cardioprotective and neuroprotective benefits by attenuating oxidative stress and maintaining redox balance in ISP-induced MI, suggesting their potential as effective pretreatment strategies to mitigate the systemic complications associated with myocardial infarction.